Youth and beauty art of the American twenties - Carbone, Teresa A. (Brooklyn Museum, 2011)
Accompanying a nationally touring exhibition, this critical history of American art of the 1920s provides a fresh perspective on the strikingly original modernist imagery of the Jazz Age. Youth and Beauty is the first wide-ranging look at American art during the period following the Great War and before the onset of the Great Depression. This illustrated volume captures a glimpse into American life during a decade when urbanization, industrialization, and mechanization were revolutionizing the United States. With more than 200 illustrations, the book brings together an array of artists and mediums, featuring iconic and surprising works by Edward Hopper, Georgia O'Keeffe, Stuart Davis, Marsden Hartley, Aaron Douglas, Alfred Stieglitz, Isamu Noguchi, Charles Sheeler, Man Ray, Walker Evans, and others.